Disproportionate Negative Impact of the Radiation Oncology Alternative Payment Model on Rural Providers: A Cost Identification Analysis of Medicare Claims. Issue 12 (December 2021) - Mantz, Constantine A.; Thaker, Nikhil G.; Pendyala, Praveen; Hubbard, Anne; Eichler, Thomas J.; Shah, Chirag; Orio, Peter F.; Petereit, Daniel G.
Abstract : PURPOSE: The Radiation Oncology Alternative Payment Model (APM) is a Medicare demonstration project that will test whether prospective bundled payments to a randomly selected group of physician practices, hospital outpatient departments, and freestanding radiation therapy centers reduce overall expenditures while preserving or enhancing the quality of care for beneficiaries. The Model follows a complicated pricing methodology that blends historical reimbursements for a defined set of services made to professional and technical providers to create a weighted payment average for each of 16 cancer types. These averages are then adjusted by various factors to determine APM payments specific to each participating provider. METHODS: This impact study segregates APM participants into rural and urban groups and analyzes the effect of the Radiation Oncology Alternative Payment Model on their fee-for-service reimbursements. RESULTS: The main findings of this study are (1) the greater net-negative revenue impact on rural facilities versus urban facilities that would have participated in the Model this year and (2) the relative lack of high-value treatment services (ie, stereotactic radiotherapy and brachytherapy) delivered by rural facilities that exacerbates their negative impact. CONCLUSION: As such, rural providers participating in the Model in its current form may face greater risk to their economic viability and greater difficulty in funding technology improvements necessary for the achievement of high-quality care compared with their urban counterparts.